HYDROTHERMAL GROWTH AND SQUEEGEE METHOD IN THE FABRICATION OF MIXED-PHASE TiO2 NANOSTRUCTURES - Muqoyyanah, Muqoyyanah; Abu Bakar, Suriani; Mohamed, Azmi; Hashim, Norhayati; Mamat, Mohamad Hafiz; Malek, Mohamad Firdaus; Ahmad, Mohamad Khairul (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2016)
In this work, the modification of TiO2 nanostructures based on its morphology and crystallinity phase were fabricated using a simple method. Hydrothermal growth method was used to synthesize nanorods and nanoflowers, while nanoparticles was applied using squeegee method. The average length and diameter of the as-grown nanorods were 3.5 and 46-215 nm, respectively. Meanwhile, the average total thickness and band gap value of mixed-phase TiO2 nanostructures were 15.98-24.54 nm and 2.84 eV, respectively. Based on its structural and electrical properties, the fabricated film has great potential to be applied as photoanode semiconductor layer for dye-sensitized solar cells application.Â Key words: TiO2, Nanostructures, Mixed-phase, Hydrothermal, Squeegee